Emergence of Norovirus GII/4 2006a and 2006b variants in hospitalized children with acute gastroenteritis in Thailand - Aksara Thongprachum (2018)
Background: Norovirus (NoV) is recognized as a significant cause of acute gastroenteritis in infants and young children worldwide. This study investigated the prevalence of NoV infection in hospitalized children with gastroenteritis in Chiang Mai, Thailand in 2006. Methods: A total of 156 fecal specimens were collected from children with diarrhea admitted to McCormick Hospital in 2006. All fecal specimens were examined for NoV by RT-PCR and the genotypes were identified by sequence analysis. Results: A high prevalence of NoV infection was detected (20.5%, 32/156). NoV GII/4 was the most predominant genotype with a prevalence of 87.5% (28/32), while GII/3, GII/6, GII/12, and GII/15 were less common (3.1% each). Among GII/4 strains, 2006b variant (75%, 21/28) emerged as the leading strain and dominated over the Hunter'04-Iike variant, which was the most common strain in the previous season of 2005. In addition, the 2003, 2004, and 2006a variants were also detected. NoV infections were most commonly observed in the rainy season in Thailand. Conclusions: This study demonstrated the emergence of GII/4 2006b variants as the major pathogen causing acute gastroenteritis among infants and children at the age of less than 5 years old who admitted to hospital in Chiang Mai, Thailand in 2006. Additionally, other GII/4 variants of 2003, 2004, and 2006a were also reported.